An ABC Optimized Biometric based User Authentication in WSN - Ramakrishnan, M; Thamaraiselvi, D (International Journal of Computer Sciences and Engineering, 2025)
User authentication is a crucial service in wireless sensor networks (WSNs) because wireless sensor nodes are typically deployed in an unattended environment, leaving them open to possible hostile network attack. The main goal of research is to Authenticate remote user in a convenient and Secured manner. In this paper, we propose a ABC( Artificial Bee Colony optimization algorithm for matching)algorithm for user authentication in hierarchical wireless sensor networks using Biometric (finger print)data. In the proposed scheme ABC algorithm calculates the standard deviation(threshold value) from the biometric data (finger print) which is used for user authentication with maximum fitness in an optimized and secured manner.